brModeloWeb: Ten Years of History and a New Extension for the Logical Design of NoSQL Databases - Souza Neto, Milton Bittencourt de; Mello, Ronaldo dos Santos (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2026)
The brModelo initiative began in 2005 with the purpose of providing semiautomated solutions to assist Database modeling education. Supported by the UFSC Database Group, the initiative comprises a set of tools developed over these 21 years, of which brModeloWeb is the most recent. Available since 2016, brModeloWeb reaches 10 years of existence with more than half a million registered users from universities and professionals that adopt it for both educational and real-world database design. This paper celebrates the successful adoption of brModeloWeb and presents a new extension for NoSQL logical design, introduced in the latest release, along with performance improvements. A usability evaluation conducted during a workshop at the Brazilian Database School (ERBD 2026) indicated that the tool was well received.